Nanometer-level temperature mapping of Joule-heated carbon nanotubes by plasmon spectroscopy. (5th January 2023) - Cretu, Ovidiu; Tang, Dai-Ming; Lu, Da-Bao; Da, Bo; Nemoto, Yoshihiro; Kawamoto, Naoyuki; Mitome, Masanori; Ding, Zejun; Kimoto, Koji
Abstract: We map the temperature distribution of suspended carbon nanotubes down to the 5-nm level inside a transmission electron microscope, by using electron energy-loss plasmon spectroscopy. The nanotubes are Joule heated in-situ, by individually contacting them using a biasing holder. The nanotubes can withstand current densities of over 5 × 10 7 A/cm 2 and temperatures of over 2000 K without breaking. The temperature reaches its maximum around the nanoprobe contact, due to the comparatively large electrical resistance and small thermally-conductive area. The temperature remains high along the entire length of the CNTs, due to the excellent in-plane thermal conductivity (up to 2800 W/m/K) of the graphitic lattice. These results verify the expected robustness of these structures and confirm them as ideal candidates for applications as interconnects under extremely high current densities and temperatures. Graphical abstract: Image 1 Highlights: Temperature of suspended Joule-heated CNTs is mapped with 5-nm resolution in a TEM. CNTs can withstand over 2000 K, more than 1000 K higher than previously measured. Hot-spot near smaller electrical contact due to high resistance and low heat transfer. High temperature along the entire CNT length because of high thermal conductivity.